2012
DOI: 10.1159/000335467
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Adverse Outcome in Patients Hospitalised for Exacerbation of Chronic Obstructive Pulmonary Disease

Abstract: Background: It is crucial to identify risk factors for poor evolution of patients admitted to hospital with chronic obstructive pulmonary disease (COPD) in order to provide adequate intensive therapy and closer follow-up. Objectives: To identify predictors of adverse outcomes in patients hospitalised for exacerbation of COPD. Methods: A prospective, observational study was conducted in patients admitted for exacerbation of COPD. Demographic and clinical parameters were evaluated, including different multidimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
82
0
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 95 publications
(97 citation statements)
references
References 78 publications
(98 reference statements)
10
82
0
5
Order By: Relevance
“…Additionally, according to a univariate analysis, we detected two statistically significant predictors of the need to initiate NIV: PaCO2 and FEV1% predicted. It is reasonable that both the PaCO2 and FEV1% predicted, which are established prognostic factors in patients with COPD, are also predictors of the need to initiate NIV during exacerbation, given that the need for NIV support implies the development of severe respiratory failure associated with a poor prognosis (1,(24)(25)(26)(27)(28)(29). However, it is noteworthy that, in the multivariate logistic regression analysis, the severity of airway obstruction assessed according to the FEV1% predicted was no longer identified as a predictor.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Additionally, according to a univariate analysis, we detected two statistically significant predictors of the need to initiate NIV: PaCO2 and FEV1% predicted. It is reasonable that both the PaCO2 and FEV1% predicted, which are established prognostic factors in patients with COPD, are also predictors of the need to initiate NIV during exacerbation, given that the need for NIV support implies the development of severe respiratory failure associated with a poor prognosis (1,(24)(25)(26)(27)(28)(29). However, it is noteworthy that, in the multivariate logistic regression analysis, the severity of airway obstruction assessed according to the FEV1% predicted was no longer identified as a predictor.…”
Section: Discussionmentioning
confidence: 98%
“…Consequently, the PaCO2 is regarded to be a poor prognostic indicator in general and has been demonstrated to be associated with the development of COPD-AE (1,7,(24)(25)(26)(27)(28)(29)(30). However, the majority of studies have focused on severely hypoxemic patients requiring NIV or patients who had previously experienced COPD-AE.…”
Section: Discussionmentioning
confidence: 99%
“…The combination of all these factors leads to diminished QoL, reduced exercise tolerance, increased risk of cardiovascular morbidity and greater risk of death [10]. In addition, it has been demonstrated that patients with previous exacerbation of COPD, hypercapnia and hypoxemia had the highest risk of an unfavorable evolution of the disease [11].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, general blood gas alterations [12,14,16,[18][19] , in particular hypercapnia [12,14,19] or hypoxaemia [18,19] , have been found to be strong predictors of mortality. Notably, a very recent study [12] demonstrates that the severity of respiratory acidosis in AECOPD increases progressively the risk of death during hospitalization (pH = 7.25-7.35 versus pH > 7.35 Odds Ratio-OR = 1.58 with a 95% Confidence Interval-CI 1.28-1.94; pH < 7.25 versus pH > 7.35 OR = 2.31, 95% CI 1.72-3.10).…”
Section: Introductionmentioning
confidence: 99%
“…Starting from the concept that a predictor of a 30-day readmission is the variable ≥ 2 previous exacerbation in a period of 1-year prior to index hospitalization (Hazard Ratio-HR = 2.47, 95% CI 1.51-4.05, p < 0.001) [23] , the relationship in the events of AECOPD between the past and the prognosis is very close. Moreover, a study published in 2012 reported the presence of at least one previous exacerbation of COPD in the previous year [OR = 3.9, 95% CI 1.6-9.9, p = 0.004)] [19] as an independent predictor of adverse outcome defined by death during hospitalisation or the 1-month follow-up.…”
Section: Introductionmentioning
confidence: 99%